Children migrants & Third Culture Kids. Roots and Routes. International Conference: June 7-9, 2013, Jagiellonian University, Kraków, Poland - Trąbka, Agnieszka (Lidé města, 2013)
The period of the late 20th and early 21st centuries is sometimes called "the age of migration" (Castles and Miller 2009). The number of migrants is estimated at 214 million people, which means that they would constitute the fifth most populous country in the world.